A Novel Sediment Microbial Fuel Cell Based Sensor for On‐Line and in situ Monitoring Copper Shock in Water. Issue 11 (14th September 2018) - Wu, Shaosong; Deng, Huan; Han, Cheng; Liu, Li; Zhong, Wenhui
Abstract: To online and in situ monitor the heavy metal shock in water, a novel sediment microbial fuel cell based sensor was developed with anode being inserted into flooded soil and cathode submerged in overlaying water. Immediately after CuSO4 solutions were added into the overlaying water, the voltage signal generated by the sensor reached a peak and the increment from baseline voltage to peak voltage increased linearly with Cu 2+ concentrations up to 160 mg L −1 . After Cu 2+ shock, charge transfer resistance ( R ct ) of anode and cathode was determined by using electrochemical impedance spectroscopy. Soil DNA and RNA was extracted and 16S rRNA and 16S rRNA gene of dominant exoelectrogenic bacteria ( Geobacter and Clostridium ) was quantified. Result showed that Cu 2+ shock decreased cathodic charge transfer resistance ( R ct ) but did not affect anodic R ct . The addition of 320 mg L −1  Cu 2+ significantly reduced abundance and activity of Geobacter and Clostridium in surface soil (0–3 cm in depth) but had no effect on exoelectrogenic bacteria in deeper soil. Moreover, baseline voltage was stable after Cu 2+ shock. The result indicates that the sensor could online and in situ monitor Cu 2+ shock which increased voltage signal by promoting cathodic reaction without dramatically inhibiting exoelectrogenic bacteria. Abstract :